Design of Stocking Density of Broilers for Closed House in Wet Tropical Climates - A Yani; H Suhardiyanto; . Erizal; B P Purwanto (Media Peternakan, 2014)
The objectives of this research were to: 1) design the stocking density of broiler reared at a closed house system in wet tropical climates based on the heat released by broiler, 2) design broiler harvesting system based on the housing heat load, and 3) design required housing area based on the broiler age. The housing design used to determine the broiler stocking density was based on Computational Fluid Dynamics (CFD) with Solid Works Flow Simulation software. The method had good validation shown by small number of average percentage of deviation (6.07%). Simulation was carried out by changing the number of broilers i.e. 16, 18, 20, 21 and 22 birds/m2. According to the CFD simulation result, total heat load inside the house was 233.33 kW at 21 birds/m2 at weight 1.65 kg/bird. At that stocking density the housing can be occupied by 27,224 birds until 22 days of age. The highest total weight was produced by daily harvesting started from 22 to 32 d. It can be concluded that the stocking density of closed house for broiler is 34.65 kg/m2, total production is 45,717 kg per period and the required area for 27,224 broilers is  248.63 m2 (1 to 7 days of age broiler), 562.52 m2 (8 to 14 days of age broiler) and 1,000 m2 (15 to 22 days of age broiler). Key words: broiler, computational fluid dynamics, stocking density, total heat